2021
DOI: 10.31557/apjcc.2021.6.4.397-405
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge of Colorectal Cancer in Qassim Region, Saudi Arabia

Abstract: Objective: Colorectal cancer (CRC) is a common and deadly disease. It is the third common malignancy in the world and the second leading cause of cancer-related deaths. Both environmental and genetic factors influence the risk of developing CRC. The clinical symptoms develop late in the course of the disease, and precursor lesions (adenomas) can be easily detected and removed. This study intends to evaluate the awareness of CRC in an Al-Qassim region and identify the (population) that can benefit from awarenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…The population's awareness of sex as a risk factor for CRC was the least known factor among the factors (33.3%), which was in line with that found by Althobaiti and Jradi (48.8%) [50] but higher than what was reported by Taha et al (20.3%) [21]. Less than two-thirds of participants were aware of the role of family history or genetics in CRC, which was more than found in a study conducted in Saudi Arabia (20.9%) [51] and less than that reported by Althobaiti and Jradi (77.59%) [50] and Saeed et al (73.5%) [18]. Participants were aware that obesity was a risk factor for CRC (Do you think that obesity is a risk factor for CRC?).…”
Section: Discussionsupporting
confidence: 86%
“…The population's awareness of sex as a risk factor for CRC was the least known factor among the factors (33.3%), which was in line with that found by Althobaiti and Jradi (48.8%) [50] but higher than what was reported by Taha et al (20.3%) [21]. Less than two-thirds of participants were aware of the role of family history or genetics in CRC, which was more than found in a study conducted in Saudi Arabia (20.9%) [51] and less than that reported by Althobaiti and Jradi (77.59%) [50] and Saeed et al (73.5%) [18]. Participants were aware that obesity was a risk factor for CRC (Do you think that obesity is a risk factor for CRC?).…”
Section: Discussionsupporting
confidence: 86%
“…Despite a well-established healthcare system in KSA; diagnosis at late stages with regional and distal metastasis of up to 50% was observed in Saudi patients with CRC diagnosis (Figure 3). Insufficient Knowledge about CRC, a possible factor for late presentation, was reported among Saudi population (Alsulaim et al, 2021) In young Saudi patients with CRC, the disease presents with more advanced stages and poorly differentiated tumors than in older patients (Al-Ahwal, Alghamdi, 2005). Adenocarcinoma is the most frequent histopathological type accounted to 79.5% of CRC in Saudi males and 82% in Saudi females (Table 4).…”
Section: Epidemiological Aspects Of Crc In Saudi Arabiamentioning
confidence: 99%
“…In the Gulf Corporation Countries (GCC) and Middle East region, several studies have pointed out the lack of knowledge and awareness regarding CRC etiology and prevention among the general population (Su et al, 2013;Qadir and Ghalia, 2018;Al-Azri et al, 2019;Althobaiti and Jradi, 2019;Tfaily et al, 2019). A recent study from Saudi Arabia revealed moderate knowledge of the clinical manifestations and risk factors toward CRC, but a low percentage of participants acknowledged the role of fatty foods as a risk factor (AlSulaim et al, 2021). In a study among adults in the UAE, a poor knowledge score was reported among older adults (≥ 50 years old) about the risk factors and screening of CRC, while having a personal or family history of cancer was directly associated with the level of awareness (Al-Sharbatti et al, 2017).…”
Section: Introductionmentioning
confidence: 99%